The effect of Islamic Revolution of Iran on the Growth of Political Islam of Iraq (1979-1989( - Yousef, Khalat M. (Humanities Journal of University of Zakho, 2016)
This study includes the effect of the Islamic revolution in Iran on the prosperity and growth of the political Islam of currents, movements, and parties in Iraq during the role of Imam Ruh Allah Al-Kumaini (1979-1989). This study is specialized on the concept of "exporting the Islamic Revolution" which is considered one of the most important political and religious concepts of the Islamic revolution in Iran . It consists of an introduction and three main sections which included a historical background on the role of Islamic institution and the rise of the Islamic revolution in Iran. It also included the ideological dimensions in creating the external politics. Finally, the effects of this revolution were on the development and growth of political Islam on Iraq in general. The study has included by results that the research has got it.